Clinical Efficacy Evaluation for Treating Trigeminal Neuralgia Using a Personalized Digital Guide Plate-Assisted Temperature-Controlled Radiofrequency. Issue 5 (July 2018) - Zhao, Suli; Deng, Mohong; Cai, Hengxing; Meng, Qinggong; Fang, Wei; Ke, Jin; Long, Xing
Abstract : Abstract: The aim of this study was to explore the application and efficacy of personalized digital guiding plate-aided radiofrequency in treating trigeminal neuralgia (TN). A total of 117 cases (93 patients) of TN from January 2015 to December 2016 were divided into the study group (n = 53) and the traditional group (n = 64). Patients in the study group were treated by the radiofrequency through a personalized digital guiding plate, whereas those in the traditional group were treated by the traditional method. We found that no significant difference between these 2 groups in age, sex, and divisions affected (V2, V3 ). However, the values for operation time, recurrence rate, and patient's satisfaction in the plate assisted group were significantly improved compared with those in the traditional group. Therefore, the personalized digital guiding plate-assisted radiofrequency has higher application value than traditional method.